High Molecular Weight Polybenzimidazole Membranes for High Temperature PEMFC. Issue 1 (6th December 2013) - Yang, J. S.; Cleemann, L. N.; Steenberg, T.; Terkelsen, C.; Li, Q. F.; Jensen, J. O.; Hjuler, H. A.; Bjerrum, N. J.; He, R. H.
Abstract High temperature operation of proton exchange membrane fuel cells under ambient pressure has been achieved by using phosphoric acid doped polybenzimidazole (PBI) membranes. To optimize the membrane and fuel cells, high performance polymers were synthesized of molecular weights from 30 to 94 kDa with good solubility in organic solvents. Membranes fabricated from the polymers were systematically characterized in terms of oxidative stability, acid doping and swelling, conductivity, mechanical strength and fuel cell performance and durability. With increased molecular weights the polymer membranes showed enhanced chemical stability towards radical attacks under the Fenton test, reduced volume swelling upon the acid doping and improved mechanical strength at acid doping levels of as high as about 11 mol H3PO4 per molar repeat polymer unit. The PBI‐78kDa/10.8PA membrane, for example, exhibited tensile strength of 30.3 MPa at room temperature or 7.3 MPa at 130 °C and a proton conductivity of 0.14 S cm–1 at 160 °C. Fuel cell tests with H2 and air at 160 °C showed high open circuit voltage, power density and a low degradation rate of 1.5 μV h–1 at a constant load of 300 mA cm–2.